Annual Update in Intensive Care and Emergency Medicine 2016 - Vincent, Jean-Louis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The Annual Update compiles the most recent developments in experimental and clinical research and practice in one comprehensive reference book. The chapters are written by well recognized experts in the field of intensive care and emergency medicine. It is addressed to everyone involved in internal medicine, anesthesia, surgery, pediatrics, intensive care and emergency medicine.
Part I. Infections and antibiotics -- Interpreting Procalcitonin at the Bedside -- Reducing Antibiotic Use in the ICU: A Time-based Approach to Rational Antimicrobial Use -- Plasmacytoid Dendritic Cells in Severe Influenza Infection -- Critically Ill Patients with Middle East Respiratory Syndrome Coronavirus Infection -- Part II. Sepsis -- Immunomodulation: The Future for Sepsis? -- Norepinephrine in Septic Shock: Five Reasons to Initiate it Early -- Myths and Facts Regarding Lactate in Sepsis -- Part III. Renal issues -- Creatinine-based Definitions: From Baseline Creatinine to Serum Creatinine Correction in Intensive Care -- The Detrimental Cross-talk between Sepsis and AKI: New Pathogenic Mechanisms, Early Biomarkers and Targeted Therapies -- Timing of Acute Renal Replacement Therapy -- (Multiple) Organ Support Therapy beyond AKI -- Part IV. Fluid therapy -- Crystalloid Fluid Therapy -- Balanced Crystalloids for Septic Shock Resuscitation -- Part V. Bleeding -- Emergency Reversal Strategies for Anticoagulants and Anti-platelet Agents -- Part VI. Cardiovascular system -- Bedside Myocardial Perfusion Assessment with Echocardiography Contrast -- Pathophysiological Determinants of Cardiovascular Dysfunction in Septic Shock -- Cardiovascular Response to ECMO -- Mechanical Circulatory Support in the New Era: An Overview -- Part VII. Cardiac arrest -- Cardiac arrest in the Elderly: Epidemiology and Outcome -- Regional Systems of Care: The Final Link in the (3z(BChain of Survival(3y (BConcept for Out-of-hospital Cardiac Arrest -- Cardiac Arrest Centers -- Part VIII. Oxygenation and respiratory failure -- High-flow Nasal Cannula Oxygen Therapy: Physiological Effects and Clinical Data -- The Potential Value of Monitoring the Oxygen Reserve Index in Patients Receiving Oxygen -- Variable Ventilation from Bench to Bedside -- Monitoring Respiratory Effort by Means of the Electrical Activity of the Diaphragm -- Dissipated Energy is a Key Mediator of VILI: Rationale for using Low Driving Pressures -- Corticosteroids as Adjunctive Therapy in Severe Community-acquired Pneumonia -- Part IX. Abdominal issues -- The Neglected Role of Abdominal Compliance in Organ-organ Interactions -- Part X Metabolic support -- Metabonomics and Intensive Care -- The Rationale for Permissive Hyperglycemia in Critically Ill Patients with Diabetes -- Indirect Calorimetry in Critically Ill Patients. Concept, Current Use, and Future Challenges -- Part XI. Ethical issues -- Managing Intensive Care Supply-demand Imbalance -- Advances in the Management of the Potential Organ Donor after Neurologic Determination of Death -- Humanizing Intensive Care: Theory, Evidence and Possibilities -- Part XII. Applying new technology -- Ultrasound Simulation Education for Intensive Care and Emergency Medicine -- Virtual Patients and Virtual Cohorts: A New Way to Think about the Design and Implementation of Personalized ICU Treatments -- Part XIII. Intensive care unit trajectories: The bigger picture -- Predicting Cardiorespiratory Instability -- Long-term Outcomes after Critical Illness Relevant to Randomized Clinical Trials -- Long-term Consequences of Acute Inflammation in the Surgical Patient: New Findings and Perspectives -- Kairotropy: Discovering Critical Illness Trajectories using Clinical Phenotypes with Big Data.s
Keywords: Medicine; Emergency medicine; Critical care medicine; Internal medicine; Medicine & Public Health; Intensive / Critical Care Medicine; Emergency Medicine; Internal Medicine; Electronic books